High clonality of Mycobacterium avium subsp. paratuberculosis field isolates from red deer revealed by two different methodological approaches of comparative genomic analysis - Turco, Silvia; Russo, Simone; Pietrucci, Daniele; Filippi, Anita; Milanesi, Marco; Luzzago, Camilla; Garbarino, Chiara; Palladini, Giorgia; Chillemi, Giovanni; Ricchi, Matteo (Frontiers in Veterinary Science, 2024)
Mycobacterium avium subsp. paratuberculosis (MAP) is the aetiological agent of paratuberculosis (Johne's disease) in both domestic and wild ruminants. In the present paper we investigated, through a Whole Genome Sequence (WGS) approach, the genetic diversity of 15 Mycobacterium avium field strains isolated in the last 10 years from red deer inhabiting the Stelvio National Park and affected by paratuberculosis. Combining de novo assembly and reference-based method, followed by a pangenome analysis, we highlight a very close relationship among 13 MAP field isolates, suggesting that a single infecting event occurred in this population. Moreover, two isolates have been classified as Mycobacterium avium subsp. hominissuis, distinct from the other MAPs under comparison but close to each other. This is the first time that this subspecies is found in Italy, in samples without evident epidemiological correlations, having been isolated in two different locations of the Stelvio National Park and in different years. Our study underlines the importance of a multidisciplinary approach incorporating molecular epidemiology and ecology into traditional infectious disease knowledge in order to investigate the nature of infectious disease in wildlife populations.